Reconciling Conflicting Jurisprudence: A Critical Analysis of the Admissibility of Unregistered Land Instruments in Nigerian Property Law - Omoigberale, Omonye (ABUAD Law Journal, 2025)
This study examined the admissibility of unregistered land instruments in Nigeria, emphasising the legal uncertainty arising from inconsistent judicial interpretations. While the Land Instruments Registration Law establishes registration as a prerequisite for legal recognition and evidentiary value, Supreme Court decision in Benjamin v Kalio, Anagbado v Faruk, and Abdullahi v Adetutu have introduced doctrinal contradictions, undermining predictability in property law jurisprudence. The research interrogates the hierarchical primacy of these decisions, questioning whether precedence should favour the most recent judgment or the depth of judicial reasoning underpinning each case. Adopting a doctrinal methodology grounded in historical analysis, the study identifies a shift toward purposive interpretation in judicial reasoning. The findings underscore the need for harmonised land registration laws and the establishment of clear evidentiary standards to reconcile these inconsistencies. By advocating for a flexible legal framework that integrates formal registration requirements with equitable considerations, the study contributes to property law scholarship by proposing a pathway to enhanced coherence and stability in Nigeria’s legal system. Such reforms aim to safeguard justice in land disputes while reinforcing the integrity and functionality of land registration processes.